Online Survey of Medical and Psychological Professionals on Structured Instruments for the Assessment of Work Ability in Psychiatric Patients - Schleifer, Roman; Gamma, Alex; Warnke, Ingeborg; Jabat, Mounira; Rössler, Wulf; Liebrenz, Michael (Frontiers in Psychiatry, 2018)
Objective To evaluate perceived needs and difficulties related to instruments for assessing work ability in individuals with mental disorders. Method We conducted an online survey of 104 German-speaking medico-legal experts (forensic psychiatric and psychological experts, insurance physicians), and therapists. Results The large majority of respondents reported they would welcome a standardized, structured instrument for the assessment of work ability. High predictiveness, inter-rater agreement, comprehensibility for laymen, and symptom validity were desired in roughly equal measure as the main characteristic of such an instrument. More women than men, and more medico-legal experts than therapists, considered symptom validation as always necessary. Pain, personality, and affective disorders were perceived to be the most difficult disorders in the context of work ability assessments. Conclusion Our survey documents professionals' wish for a structured assessment of work ability in both medico-legal and therapeutic settings.